COMPARATIVE STUDY OF ECOTOURISM PRACTICES IN U ZBEKISTAN AND GERMANY (International journal of artificial intelligence, 2025)
Ecotourism has emerged as a vital component of sustainable tourism strategies across the world. This article offers a comparative analysis of ecotourism practices in Uzbekistan and Germany, examining how each country approaches environmental preservation, community involvement, and sustainable development through tourism. While Germany has a well-established ecotourism framework grounded in policy, regulation, and green infrastructure, Uzbekistan’s ecotourism is evolving, centered around its rich natural landscapes and growing interest in sustainability. By comparing the two, this study highlights the strengths, challenges, and opportunities present in both contexts.